2006
DOI: 10.1074/jbc.m604476200
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the RNA Interference Effector Protein Ago1 and 14-3-3 Proteins

Abstract: Here, we provide evidence that the amino terminus of Ago1 binds to proteins that function in cell cycle regulation including 14-3-3 proteins. Interestingly, the amino terminus of human Ago2, the endonuclease that cleaves siRNA-targeted mRNAs, was also demonstrated to bind 14-3-3 proteins. Overexpression of the Ago1 amino terminus in yeast resulted in cell cycle delay at the G 2 /M boundary. Further investigation revealed that nuclear import of the mitosis-inducing phosphatase Cdc25 is inhibited by overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 36 publications
(33 reference statements)
1
20
0
Order By: Relevance
“…BA also induced distinct G 2 /M phase arrest and apoptosis in AGS cells, accompanied with typical apoptotic morphological changes. It have been revealed numerous pro-apoptosis and cell cycle proteins (eg, Cyclin B1, CyclinD1 and Bcl-x L ) were targeted by BA [15][16][17] . Because Bcl-x L , Cyclin D1 and Cyclin B1 gene expression modulated by BA is regulated by Piwi protein, we investigated whether the anticarcinogenic effect of BA was mediated through modulation of Hiwi and Hiwi-regulated gene products.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…BA also induced distinct G 2 /M phase arrest and apoptosis in AGS cells, accompanied with typical apoptotic morphological changes. It have been revealed numerous pro-apoptosis and cell cycle proteins (eg, Cyclin B1, CyclinD1 and Bcl-x L ) were targeted by BA [15][16][17] . Because Bcl-x L , Cyclin D1 and Cyclin B1 gene expression modulated by BA is regulated by Piwi protein, we investigated whether the anticarcinogenic effect of BA was mediated through modulation of Hiwi and Hiwi-regulated gene products.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the Piwi in yeast resulted in cell cycle delay at the G 2 /M boundary [17] . For example in Drosophila, altering the expression level of Piwi leads to changes in the proliferation rate of germline stem cells [18] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, genetic analyses of patterning and morphogenesis in Drosophila embryos have revealed an essential role for the N-terminal glutamine-rich repeats of AGO2-slicer (11) and the N-terminal half of Schizosaccharomyces pombe AGO1, including the PAZ domain, has been shown to bind to proteins involved in cellcycle regulation (12). Furthermore, in vivo studies from our laboratory have indicated that the N-terminal 68 amino acids of Trypanosoma brucei AGO1 (termed the RGG domain, because it includes ten arginine-glycine-glycine or RGG motifs) is an important determinant for the RNAi response (13).…”
mentioning
confidence: 99%